Brain and liver pathology, amyloid deposition, and interferon responses among older HIV-positive patients in the late HAART era. Issue 1 (December 2017) - Solomon, Isaac; De Girolami, Umberto; Chettimada, Sukrutha; Misra, Vikas; Singer, Elyse; Gabuzda, Dana
Abstract Background HIV+ patients on highly active antiretroviral therapy (HAART) with suppressed viral loads have a low incidence of HIV-associated dementia, but increased prevalence of milder forms of HIV-associated neurocognitive disorders (HAND). These milder forms of HAND are often associated with minimal histological abnormalities, and their pathophysiology is unclear. Comorbidities, altered amyloid metabolism, accelerated brain aging, and activated interferon responses are suspected to play a role in HAND pathogenesis in HAART–treated persons. Methods To investigate associations between liver disease, accelerated brain aging, and HAND in HIV+ patients in the late HAART era (2002–2015), we studied liver and brain autopsy tissues from 53 older subjects evaluated at UCLA and BWH using histopathological stains, a sensitive fluorescent amyloid stain (AmyloGlo), and targeted gene expression profiling (NanoString). Results The majority of HIV+ subjects (median age 56) were on HAART (89.3%) with last pre-mortem plasma viral load <400 copies/mL (81.5%); 50% had CD4+ counts <200 cells/μL. Compared to HIV- controls (median age 65), HIV+ subjects had more cancer (p = 0.04), illicit drug use (p <0.00001), and HCV co-infection (p = 0.002), less cardiovascular disease (p = 0.03), and similar prevalence of cerebrovascular disease ( 40%), hypertension, hyperlipidemia, and diabetes. Deep frontal white matter showed increased gliosis in HIV+ subjects vs. HIV- controls (p = 0.09), but no significant differences in myelin loss, blood vessel thickening, or inflammation. Liver showed more severe fibrosis/cirrhosis (p = 0.02) and less steatosis (p = 0.03) in HIV+ subjects, but no significant differences in inflammation, blood vessel thickness, or pigment deposition. There were no significant associations between liver and brain pathologies. AmyloGlo staining detected large amyloid deposits in only one HIV+ case (age 69 with Alzheimer's disease pathology) and two HIV- controls (ages 66 and 74). White matter from HIV+ cases vs. HIV- seronegative controls showed a trend (p = 0.06) towards increased interferon response gene expression (ISG15, MX1, IFIT1, IFIT2, and IFITM1). Conclusions Gliosis and cerebrovascular disease, but not accelerated amyloid deposition, are common brain pathologies among older HIV+ patients in the late HAART era. Although HIV+ subjects had more cirrhosis, liver pathology was not associated with any consistent pattern of brain pathology. Cerebrovascular disease, interferon responses, and neuroinflammation are likely factors contributing to brain aging and HAND in older HIV+ patients on current HAART regimens.